2015
DOI: 10.3390/atmos6111801
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 Concentration Differences between Various Forest Types and Its Correlation with Forest Structure

Abstract: Abstract:The Plain Forestation Project is an important measure designed to alleviate air pollution in Beijing, the capital of China. Ten commonly cultivated forest types of the Plain Forestation Project were studied at three growth stages of leaves. The particulate matter (PM)2.5 concentrations and forest structures were surveyed to analyze the PM2.5 concentration differences between different forest types, and establish a linear relationship between forest structures and PM2.5 concentration differences. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…The variations in particulate retention among tree species in this study were consistent with those found by Liu [12] and Yang [45] and may be explained by variations in morphological characteristics that enable plants to trap particulates (e.g., canopy structure, leaf density, leaf surface roughness, and wax) [16]. The three-dimensional structure of tree canopies encourages turbulent air movement and the more complex the canopy structure, the more particulates are deposited onto leaf surfaces [46].…”
Section: Individual Functionssupporting
confidence: 92%
See 1 more Smart Citation
“…The variations in particulate retention among tree species in this study were consistent with those found by Liu [12] and Yang [45] and may be explained by variations in morphological characteristics that enable plants to trap particulates (e.g., canopy structure, leaf density, leaf surface roughness, and wax) [16]. The three-dimensional structure of tree canopies encourages turbulent air movement and the more complex the canopy structure, the more particulates are deposited onto leaf surfaces [46].…”
Section: Individual Functionssupporting
confidence: 92%
“…For instance, Jin [11] measured canopy density and LAI with a laser dust monitor and applied a mixed-effect model to quantitatively analyze the effect of particulates on vegetation. Similarly, Liu [12] used a TH-150C particulate sampler to obtain PM 2.5 concentrations in sample plots and applied a multiple regression model to analyze the relationship between PM 2.5 concentrations and NDVI and LAI. Although particle collectors can accurately capture PM 2.5 concentrations in real time, these instruments are expensive to operate.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are based on the comparison of leaf shape (linear, lanceolate, obovate, palmate, needle-like, tip-like, broad-leaved or elliptic) and leaf arrangement (opposite, alternate or whorled). As a result, the ability of the plants to capture and accumulate PM differs significantly among foliage with different morphological features [40][41][42][43][44][45]. But Daresta had different results: the arrangement of leaves had no effect on particle matters adsorption, perhaps because other characteristics of leaves had more significant effects than the leaves arrangement [46].…”
Section: Factors Of Capturing and Absorbing Pmmentioning
confidence: 99%
“…Research by Wang et al showed that particles were more easily retained if there were 1-2 µm ridged grooves on leaf surfaces or rough blade surfaces far from the rachis in broad-leaved plants [11]. Factors including leaf shape, leaf size, tree trunk and crown density explained the different capacities of PM 2.5 retention in forests [12].…”
Section: Introductionmentioning
confidence: 99%